1997
DOI: 10.1046/j.1365-2249.1997.3911292.x
|View full text |Cite
|
Sign up to set email alerts
|

A cross-reactive idiotype in scleroderma

Abstract: SUMMARYAutoantibodies to centromere proteins (anti-CENPs) and to topoisomerase-I are highly specific for scleroderma. Unlike most autoantibodies in other diseases, these autoantibodies are mutually exclusive. We have analysed the idiotypes (Ids) expressed by anti-CENP-B, antitopoisomerase-I, and IgGs from 20 scleroderma patients. Rabbit anti-Ids were prepared to antitopoisomerase-I from two scleroderma patients, and to anti-CENP-B from four patients. These six anti-Ids were used to study the purified autoantib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Taken altogether, our data suggest that the origin of these ACA may be different than that in Raynaud's disease and SSc. Our data further supports the high specificity and homogeneity of the humoral response that is unique of SSc and Raynaud's disease (12).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Taken altogether, our data suggest that the origin of these ACA may be different than that in Raynaud's disease and SSc. Our data further supports the high specificity and homogeneity of the humoral response that is unique of SSc and Raynaud's disease (12).…”
Section: Discussionsupporting
confidence: 83%
“…UNUSUAL ANTICENTROMERE ANTIBODIES serum immunoglobulins from normal individuals or patients with systemic lupus erythematosus (12,16). Furthermore, after exhaustive absorption of serum ATA and ACA, we showed that CRI-EM, while present in the affinity purified autoantibodies, was absent from the other immunoglobulins in the same individual (12,13).…”
mentioning
confidence: 72%
See 3 more Smart Citations